Бакалаврларды геометриялық-графикалық даярлауда сызба геометрия пәнінің маңызы мен қазіргі жағдайы - Karymsakov U.T. Қарымсақов У.Т.; Abildabekova D.D. Абилдабекова Д.Д. (Рroblems of engineering and professional education, 2022)
Descriptive geometry is a fundamental discipline in the formation of the geometric-graphic competence of bachelors of technical specialties. But recently this discipline is separated from the educational process, and only in the "Engineering graphics" is offered in small quantities. The article describes the importance and necessity of the descriptive geometry in the geometric and graphic preparation of bachelors of technical specialties.